Study of the Physical Properties and Compressive Strength of Karst Rocks in the Leang Londrong Cave Area Bantimurung Bulusaraung National Park - Muhammad Arsyad; Dian Mukarramah; Agus Susanto (Pascasarjana, Mataram University, 2023)
Research has been carried out on the physical properties and compressive strength of karst rocks in the Leang Londrong cave area. The purpose of this research was to analyzr the value of physical properties and compressive strength of rocks including density and porosity and also calssify limestone types based on the value of physical properties and compressive strength. The compressive strength value obtained from a non-destructive method, namely by using a Schmidt Hammer. The process starts from taking 30 rock samples in the Leang Lonrong cave area at 10 predetermined points. Based on the physical properties test of karst rocks in the Leang Londrong cave area, the rock density values are in the range of 2,60 to 2,62 , while the porosity value are in the range 0-6 %. So that the type of rock in the Leang Londrong cave area is dolomite limestone. The compressive strength value of the rock is obtained from the conversion of the Schmidt Hammer rebound value. The value of the compressive strength of karst rocks is obtained in the range of values fro, 20 MPa to 62 MPa. So that the rocks in the Leang Londrong cave area are quite hard or medium types of rock.